Faktor Sumber Daya Manusia dalam Keberhasilan Manajemen Logistik Obat di Indonesia : A Systematic Literature Review - Julia Arlianti Devani; Nadya Zahira Shafa; Kania Imanuella Rante; Chaerunnisa AR; Eka Putri Rahayu; Sumarni Sumarni; Ratno Adrianto (Lembaga Pengembangan Kinerja Dosen, 2026)
Pharmaceutical logistics management plays a critical role in ensuring that the right types of medications, in the right quantities, are delivered on time and meet quality standards at healthcare facilities. The success of this process depends not only on budgets, infrastructure, and information systems, but also on the human resources managing each stage of pharmaceutical logistics. The success of this process is influenced not only by the budget, facilities, and information systems, but also by the human resources managing each stage of pharmaceutical logistics. This study aims to analyze human resource factors in the success of pharmaceutical logistics management in healthcare facilities. The method used was a Systematic Literature Review, searching for articles via Google Scholar, Garuda, PubMed, and ScienceDirect from May to June 2026. The keywords used were related to human resources, pharmaceutical logistics management, pharmacy personnel, and pharmaceutical logistics management. Of the 50 identified articles, 20 were reviewed in full, and 13 met the inclusion criteria for further analysis. The results indicate that the competencies of pharmaceutical personnel, adequate staffing levels, training, supervision, task allocation, work coordination, workload, and the ability to use logistics information systems are the primary factors influencing the success of pharmaceutical logistics management. Weaknesses in these aspects can increase the risk of distribution delays, inaccurate stock records, dead stock, expired medications, and stock-outs. The implications of this study underscore the need to strengthen human resource capacity, implement routine supervision, establish clear task allocation, and utilize logistics information systems to enhance the effectiveness of pharmaceutical logistics management.